2001
DOI: 10.1177/089875640101800202
|View full text |Cite
|
Sign up to set email alerts
|

Mandible and Mandibular First Molar Tooth Measurements in Dogs: Relationship of Radiographic Height to Body Weight

Abstract: Height measurements of the mandible and the mandibular first molar tooth were obtained from 234 dogs. Statistical analysis was performed to determine possible associations between these measurements and body weight, sex, age, and body condition. There was a statistically significant association between the mandible: mandibular first molar tooth height measurement ratio and body weight (p < 0.0001) in all body weight groups. Small dogs had proportionally larger mandibular first molar teeth relative to mandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 10 publications
3
42
0
3
Order By: Relevance
“…9 Results of the present study indicated that there was a fairly safe region along the ventrolateral surface of the feline mandible that provides a suitable area to secure a titanium miniplate. Unlike dogs, in which the width of the mandibular region suitable for miniplate application (ie, root-ventral border length) is significantly correlated with body weight, 34 the root-ventral border length was not significantly correlated with the body weight of the feline cadavers used in this study. Instead, in cats, the width of the mandibular region suitable for miniplate application was best correlated with the CSA of the mandible immediately caudal to the mandibular first molar tooth and was correlated to a lesser degree with the overall length of the mandible.…”
Section: Discussionmentioning
confidence: 61%
“…9 Results of the present study indicated that there was a fairly safe region along the ventrolateral surface of the feline mandible that provides a suitable area to secure a titanium miniplate. Unlike dogs, in which the width of the mandibular region suitable for miniplate application (ie, root-ventral border length) is significantly correlated with body weight, 34 the root-ventral border length was not significantly correlated with the body weight of the feline cadavers used in this study. Instead, in cats, the width of the mandibular region suitable for miniplate application was best correlated with the CSA of the mandible immediately caudal to the mandibular first molar tooth and was correlated to a lesser degree with the overall length of the mandible.…”
Section: Discussionmentioning
confidence: 61%
“…A tooth index to compare the relative tooth sizes between the three different big cats was calculated for each of the three mandibular teeth (PM3, PM4 and M) based on a previous study conducted in dogs (Gioso et al ., ). The following formula was utilized to do the calculation:Toothindexfalse(Tifalse)=CrownheightMandibleheight…”
Section: Methodsmentioning
confidence: 99%
“…Restoring dental occlusion and limiting soft tissue trauma while preserving dental‐related structures are crucial to bony union of mandibular fractures . The first mandibular molar teeth are relatively large in small dogs, and their roots occupy most of the jaw bone height . These anatomical characteristics increase the risk of iatrogenic damage to local dental and neurovascular structures during placement of intraosseous metallic implants .…”
Section: Introductionmentioning
confidence: 99%
“…5,6,32 The first mandibular molar teeth are relatively large in small dogs, and their roots occupy most of the jaw bone height. 33 These anatomical characteristics increase the risk of iatrogenic damage to local dental and neurovascular structures during placement of intraosseous metallic implants. [34][35][36][37] A wire-reinforced interdental composite splint (WRICS) can be used to treat mandibular fractures located in a dentate area where canine and carnassial teeth are stable and be used to anchor interdental fixation.…”
Section: Introductionmentioning
confidence: 99%